Peritoneal lavage with sterile water reduces IL-1 levels and postoperative adhesions following laparotomy in rats - Fernandi, Ryan; Sudartana, I Ketut; Sueta, Made Agus Dwianthara; Mahayasa, I Made; Yasa, Ketut Putu; Wibawa, I Gusti Agung Bagus Krisna (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Peritoneal lavage with normal saline is common in abdominal surgeries, yet recent studies indicate that it increases intraperitoneal adhesion risks. This study compares the effects of peritoneal lavage with normal saline versus sterile water on interleukin-1 (IL-1) levels and intraperitoneal adhesion following laparotomy in rats. In this post-test control group study, 20 adult Wistar rats were subjected to laparotomy before being randomly divided into two groups to receive either intraperitoneal lavage with normal saline (0.9% NaCl) or sterile water. After 7 days, IL-1 level and degree of adhesion were evaluated. The saline group had higher adhesion levels (4 rats with grade 4, 5 with grade 3, 1 with grade 2) than the sterile water group, which had lower levels (2 rats with grade 3, 5 with grade 2, 3 with grade 1). There was a significant difference in IL-1 levels between the sterile water group (37,111.6 ± 6,535.61 pg/ml) and the normal saline group (57,456.3 ± 10,583.41 pg/ml). There was a significant correlation between IL-1 levels and adhesion grade (p=0.008). Intraperitoneal lavage with sterile water results in significantly lower adhesion grade and IL-1 levels than normal saline, suggesting its potential for reducing postoperative adhesions. Further studies are needed to elucidate the mechanism of reduced adhesion and inflammation associated with sterile water lavage.